Features of the special knowledge use in the investigation of murders committed by convicts in prisons (Law and Safety, 2022)
Negative trends in the economy and social relations are slowing down the process of reforming the economic and financial system. The sharp restriction of state control and other negative phenomena that existed in our country have caused a significant increase in crime, especially its organized forms, resulting in a sharp increase in the number of particularly serious crimes against the person. A felony such as murder committed by a convict in prison is no exception.These criminal offenses invariably cause a significant public response, because, firstly, a serious criminal offense is committed, such as murder, secondly, it is committed by convicts serving sentences, and thirdly, as a rule, this category of criminal offenses is committed in correctional facilities.Convicts are persons with criminal experience who know the peculiarities of law enforcement agencies and have techniques for counteracting the investigation of criminal offenses, so the investigator faces the difficult task of identifying and exposing both the direct perpetrators and organizers (intermediaries) of such murders. That is why it is impossible to search for, record, seize and investigate the criminologically significant information about crimes of this kind necessary for the investigation and the court without the use of various special knowledge.In addition, the continuous improvement of technical means and methods significantly expands the range of specialized knowledge, which, in turn, allows you to identify, record and remove traces that were previously unavailable for research. However, the problem is that investigators are often not fully informed about the possibilities of using expertise in the investigation of criminal offenses. It should also be borne in mind that murder of this category is committed in a specific situation, namely in correctional facilities. All the above determined the relevance of the chosen research topic.
Keywords: special knowledge; forensic examination; murder; places of imprisonment; criminal offense.